A novel and efficient surgical procedure for pyriform sinus fistulas in children - Chen, Jiarui; Wang, Ying; Shen, Chenling; Wang, Jing; Li, Xiaoyan (Frontiers in Pediatrics, 2024)
Objective This study aims to evaluate the efficacy of a novel surgical procedure for pyriform sinus fistulas in children via the external cervical approach through the hypopharynx. Methods A retrospective analysis was conducted on 71 pediatric patients with pyriform sinus fistula (PSF) who underwent treatment at the Department of Otolaryngology Head and Neck Surgery, Shanghai Children's Hospital, from 2012 July to 2022 July. Surgical treatment of PSF was performed via the external cervical approach through the hypopharynx, with dye instilled through the internal opening to serve as a guide for tract identification. Results All the internal orifices were found in the pyriform sinus by direct laryngoscopy in all 71 patients under general anesthesia. Two patients had a postoperative temporary hoarseness that resolved after 3 months. The other patients had no complications such as parapharyngeal abscess and incision infection. All patients were followed up for 23 months–70 months, and no recurrence was found. Conclusion The novel surgical procedure of PSF performed via the hypopharynx has advantages such as a short operation path, quick recovery, fewer complications, and a low recurrence rate. This method is a better choice for managing recurrence cases after repeated cauterization endoscopic surgeries, as well as for patients with visible cervical surgical scars or masses.